Membrane lipids under norm and pathology - Marzoog, Basheer Abdullah; Vlasova, Tatyana Ivanovna (European Journal of Clinical and Experimental Medicine, 2021)
<p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Lipid is an essential component of the cell and its organelles membrane. The uniqueness and selectivity of lipids to specific functions and asymmetry of lipid distribution in the organelle’s membrane give the cell ability of being highly qualified and specified. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The paper provides a comprehensive review of membrane lipids in different tissues and organelles of the cell in norm and disease. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The paper analyzed the present literature data on membrane lipids behavior in physiology and pathology. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. The major structural and functional lipids of the cell membrane are phosphatidylcholine > phosphatidylethanolamine. The absence/deficiency or augmentation of a specific type of lipid results in serious defects and usually life-threatening with a permanent disability. The observations discussed here suggest, the lipid peroxidation severity depends on the membrane lipid composition of the cell. Some tissue cells can handle lipoperoxidation and protect themselves from the peroxidation damaging products better, while other cells cannot compensate. Therefore, some organs are highly sensitive to peroxidation and irreversible changes occur rapidly. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. To sum up, the understanding of lipid’s role in norm and disease is clinically crucial to evaluate a novel therapeutic target to treat many metabolic disorders such as metabolic syndrome and some lysosomal storage disorders via targeting specific new signaling pathways, lipid molecules, and enzymes.